Starvation-induced proteasome assemblies in the nucleus link amino acid supply to apoptosis - Maxime Uriarte (Nature Portfolio, 2021)
Upon starvation, cells coordinate protein disposal to recycle amino acids, although the role of the proteasome has been unclear. Here, the authors show that in the mammalian nucleus, proteasomes form condensates that dissolve following nutrient replenishment.